PROFIL SCIENTIFIC REASONING CALON GURU SEKOLAH DASAR: BUKTI DARI KURSUS ILMU PENGETAHUAN ALAM DASAR - Susi Martini (MURABBI, 2025)
Scientific reasoning is a fundamental competence required for preservice primary teachers, particularly those who will teach science at the elementary level. Despite its importance, empirical evidence regarding the scientific reasoning profile of prospective Madrasah Ibtidaiyah (MI) teachers remains limited. This study aimed to profile the scientific reasoning skills of pre-service MI teachers enrolled in a Basic Natural Science course. A descriptive quantitative design was employed involving 35 students from a Primary Teacher Education Program. The instrument consisted of 20 items developed based on Lawson’s six dimensions of scientific reasoning: conservation, proportional reasoning, control of variables, probabilistic reasoning, correlational reasoning, and hypothetico-deductive reasoning. Data were analyzed using descriptive statistics, including mean, standard deviation, and distribution across reasoning levels. The results indicated that the overall mean score was 73.68, suggesting a moderate-to-high level of scientific reasoning. The highest performance was observed in hypothetico-deductive reasoning, whereas probabilistic and correlational reasoning yielded the lowest scores. In terms of reasoning levels, 54.29% of students were categorized at the formal reasoning level, 37.14% at the transitional level, and 8.57% at the concrete level. Although the majority of students demonstrated formal reasoning ability, substantial variability across dimensions suggests the need for instructional approaches that explicitly strengthen multivariable and probabilistic reasoning. These findings provide an empirical basis for designing inquiry-oriented instruction in Basic Natural Science courses to better prepare pre-service teachers for science teaching in primary education.